Glycine and N‐acetylcysteine (GlyNAC) supplementation in older adults improves glutathione deficiency, oxidative stress, mitochondrial dysfunction, inflammation, insulin resistance, endothelial dysfunction, genotoxicity, muscle strength, and cognition: Results of a pilot clinical trial. Issue 3 (27th March 2021) - Kumar, Premranjan; Liu, Chun; Hsu, Jean W.; Chacko, Shaji; Minard, Charles; Jahoor, Farook; Sekhar, Rajagopal V.
Abstract: Background: Oxidative stress (OxS) and mitochondrial dysfunction are implicated as causative factors for aging. Older adults (OAs) have an increased prevalence of elevated OxS, impaired mitochondrial fuel‐oxidation (MFO), elevated inflammation, endothelial dysfunction, insulin resistance, cognitive decline, muscle weakness, and sarcopenia, but contributing mechanisms are unknown, and interventions are limited/lacking. We previously reported that inducing deficiency of the antioxidant tripeptide glutathione (GSH) in young mice results in mitochondrial dysfunction, and that supplementing GlyNAC (combination of glycine and N‐acetylcysteine [NAC]) in aged mice improves naturally‐occurring GSH deficiency, mitochondrial impairment, OxS, and insulin resistance. This pilot trial in OA was conducted to test the effect of GlyNAC supplementation and withdrawal on intracellular GSH concentrations, OxS, MFO, inflammation, endothelial function, genotoxicity, muscle and glucose metabolism, body composition, strength, and cognition. Methods: A 36‐week open‐label clinical trial was conducted in eight OAs and eight young adults (YAs). After all the participants underwent an initial (pre‐supplementation) study, the YAs were released from the study. OAs were studied again after GlyNAC supplementation for 24 weeks, and GlyNAC withdrawal for 12 weeks. Measurements included red‐blood cell (RBC) GSH, MFO; plasma biomarkers of OxS, inflammation, endothelial function, glucose, and insulin; gait‐speed, grip‐strength, 6‐min walk test; cognitive tests; genomic‐damage; glucose‐production and muscle‐protein breakdown rates; and body‐composition. Results: GlyNAC supplementation for 24 weeks in OA corrected RBC‐GSH deficiency, OxS, and mitochondrial dysfunction; and improved inflammation, endothelial dysfunction, insulin‐resistance, genomic‐damage, cognition, strength, gait‐speed, and exercise capacity; and lowered body‐fat and waist‐circumference. However, benefits declined after stopping GlyNAC supplementation for 12 weeks. Conclusions: GlyNAC supplementation for 24‐weeks in OA was well tolerated and lowered OxS, corrected intracellular GSH deficiency and mitochondrial dysfunction, decreased inflammation, insulin‐resistance and endothelial dysfunction, and genomic‐damage, and improved strength, gait‐speed, cognition, and body composition. Supplementing GlyNAC in aging humans could be a simple and viable method to promote health and warrants additional investigation. Abstract : This study found that compared to healthy young adults, older humans have severely elevated oxidative stress, glutathione deficiency, impaired mitochondrial function, increased inflammation, insulin resistance and endothelial dysfunction, and lower muscle strength and mental cognition. We tested and found that supplementing GlyNAC (combination of glycine and N‐acetylcysteine) improved all these defects, and that stopping GlyNAC resulted in a loss of benefits. The results of this trial suggests that GlyNAC supplementation could be a simple, safe and effective nutritional strategy to boost cellular defenses to protect against oxidative stress, correct mitochondrial defects to improve energy availability, increase muscle strength and cognition, and thereby promote healthy aging in humans.